Positive Emotion Skills Intervention to Address Burnout in Critical Care Nurses. (2020) - Cheung, Elaine O.; Hernandez, Alison; Herold, Emma; Moskowitz, Judith T.
ABSTRACT : N/A: Critical care nurses experience high levels of workplace stress, which can lead to burnout. Many medical centers have begun offering wellness programs to address burnout in their nursing staff; however, most of these programs focus on reducing negative states such as stress, depression, and anxiety. A growing body of evidence highlights the unique, independent role of positive emotion in promoting adaptive coping in the face of stress. This article describes a novel approach for preventing burnout in critical care nurses: an intervention that explicitly aims to increase positive emotion by teaching individuals empirically supported skills. This positive emotion skills intervention has been used successfully in other populations and can be tailored for critical care nurses. Also discussed are recommendations for addressing burnout in intensive care unit nurses at both the individual and organizational levels.